Réflexions méthodologiques sur l'autoconfrontation croisée - Faïta, Daniel; Vieira, Marcos (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
We have studied and developed a methodological procedure, named cruised auto confrontation, in order to analyze work situations, with the purpose of recovering the process of production, through the understanding of the activity purpose itself. The principles of the Bakhtinian dialogism and the Vigotskyan development psychology were applied to understand linguistic interventions in professional activities. The five subsequent parts of the method help the analyst orientate his work in order to develop an action towards the subject, which is confronted with himself and with others in the activity. The method succeeded in shedding light on the relation between real activity and represented activity, taking into account speech genders and activity gender.